Multimodal Semantic Quantity Representations: Further Evidence from Korean Sign Language - Domahs, Frank; Klein, Elise; Moeller, Korbinian; Nuerk, Hans-Christoph; Yoon, Byung-Chen; Willmes, Klaus (Frontiers in Psychology, 2012)
Korean deaf signers performed a number comparison task on pairs of Arabic digits. In their RT profiles, the expected magnitude effect was systematically modified by properties of number signs in Korean Sign Language in a culture-specific way (not observed in hearing and deaf Germans or hearing Chinese). We conclude that finger-based quantity representations are automatically activated even in simple tasks with symbolic input although this may be irrelevant and even detrimental for task performance. These finger-based numerical representations are accessed in addition to another, more basic quantity system which is evidenced by the magnitude effect. In sum, these results are inconsistent with models assuming only one single amodal representation of numerical quantity.